The Structural Model of Organization Performance in Small and Medium Enterprises in Thailand Medium Enterprises in Thailand - et. al., Thawatchai Nima, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to 1. Study factors of supplier quality management and production quality management that affect organization performance.2. Confirm the structural models that affect organization performance. This study was mixed methods research. The quantitative research consisted of 13 observable variables, which collected data from 260 medium and small companies in Thailand. The qualitative research collected data from a focus group of experts involved in organizational management, quality management, and supplier management of nine experts. The research results were found that 1. The structural model of organization performance in Small and Medium Enterprises in Thailand were consistent and harmonious with empirical data, with consistency values of c2= 94.89, df = 61, c2/ df = 1.56, CFI = 0.98, GFI = 0.95, SRMR = 0.049, RMSEA = 0.046. 2. Factors affecting organization performance are factors of Supplier Quality Management, and Production Quality Management, respectively.